TRANSFER KAPITAL: Studi Praktik Ulama Dalam Pengentasan Kemiskinan di Kota Tasikmalaya, Jawa Barat - Maulana Janah (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
This study is carried out to explain a capital transfer owned by Ulama in act of eradicating poverty. Religious leaders known as ulama are intelligent individuals with traits common to the pesantren. They have their own habits, which include living in an environment where Islamic ideals are ingrained. In such contexts, there is something to do with how do the ulama go about their daily lives in a society that is always changing. This study uses a qualitative method. Inductively, it is possible to deduce the research findings from the described phenomena. The data were collected systematically through observation, interviews, and recording of data sources. The data collection took place at the Al-Amin Islamic Boarding School in Tasikmalaya City. The habitus theory is used in the study framework to examine the methods of ulama to alleviate poverty. According to the study's findings, the ulama possess socioeconomic, cultural, and symbolic capital. Transferring one capital into another is possible. In the pesantren setting, community empowerment serves as the format. Additionally, the ulama amassed material wealth in the form of religious capital and other types of capital, which improved their standing in society. The process of multiplying habits with capital strength that is gathered in the social environment that allows for a process of interaction between individuals who play a role in poverty alleviation is how the clergy practice of it.